Breast Reconstruction in Patients with Prior Breast Augmentation: Searching for the Optimal Reconstructive Option - Pasquale Tedeschi; Rossella Elia; Angela Gurrado; Eleonora Nacchiero; Alessia Angelelli; Mario Testini; Giuseppe Giudice; Michele Maruccia (Medicina)
Background and Objectives: Breast cancer in patients with prior breast augmentation poses unique challenges for detection, diagnosis, and management. Mastectomy rates are increasing, and patients with prior augmentation often have a lower body mass index, making autologous techniques unsuitable. This study aims to assess the best reconstructive option in patients with a history of subglandular or dual-plane breast augmentation. Materials and methods: A prospective analysis was conducted on patients who underwent breast reconstruction after mastectomy. Patients with subglandular or dual-plane breast augmentation were included. Patients were divided into submuscular breast reconstruction (Group 2) or prepectoral breast reconstruction (Group 1) groups. Demographic and surgical data were collected. Results: A total of 47 patients were included, with 23 in Group 1 and 24 in Group 2. Complications occurred in 11 patients (23.4%), with significant differences between groups. The most common complication was seroma formation. Implant loss occurred in 4.3% of cases in Group 1, while no implant loss was observed in Group 2. Patient-reported satisfaction scores were similar between groups at 12 months postoperatively. Conclusions: Subpectoral breast reconstruction with a tissue expander seems a safer and effective technique for patients with prior breast augmentation. It resulted in fewer complications. This approach should be considered as an option for breast reconstruction after mastectomy in this cohort of patients.